Transient Analysis and Modelling of 2nd- and 4th-Order LCLC Filter under Non-Symmetrical Control - Dobrucky, B.; Benova, M.; Kascak, S. (Elektronika ir Elektrotechnika, 2011)
The paper shows how it is possible to obtain the harmonic sinusoidal voltage on the load side at non-harmonic periodical supplying from the converters. It can be used either LCLC resonant filter for frequency of fundamental harmonic component, or LC filter tuned for switching frequency. Both filters have to remove higher harmonic components from the supplying voltage to reach the harmonic distortion roughly 5 %. The paper deals mainly with analysis and modelling of 4th order LCLC filter (of the first type) under non-symmetrical supply and with comparing to the other types of filtering. Simulation results as well as experimental verification confirm good quality of output quantities of the filter. Ill. 19, bibl. 10 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.364